Do Psychological Resilience and Emotional Intelligence Vary Among Stress Profiles in University Students? A Latent Profile Analysis - Kökçam, Büşra; Arslan, Coşkun; Traş, Zeliha (Frontiers in Psychology, 2022)
After the outbreak of the coronavirus/COVID-19, significant changes have occurred in the lifestyle of students. However, despite students’ life stress has been studied extensively with non-comprehensive scales and variable-centered approach, it has been little studied with a comprehensive scale and person-centered approach. Using the Student Life Stress Inventory-revised, we analyzed students’ latent stress profiles and examined differences in psychological resilience and emotional intelligence by comparing stress profiles from a sample of 418 undergraduate and graduate students (aged 18-36) in various departments of eight universities in Turkey. We identified five distinct stress profiles, defined as extremely low stress group (ELSG), low stress group (LSG), medium stress group (MSG), high stress group (HSG) and extremely high stress group (EHSG). We found that (1) MSG and HSG were similar in terms of emotional intelligence, resilience, having high standards, and reported higher levels of physiological, emotional, and behavioral reactions than ELSG and LSG; (2) MSG felt more pressure than HSG; (3) ELSG reported higher levels of emotional intelligence (well-being, self-control, emotionality) than others. Also, EHSG reported lower levels of emotional intelligence (specifically self-control) than others; (4) whereas resilience was highly positively correlated to well-being, resilience and well-being were moderately negatively correlated to stress. ELSG and LSG reported higher levels of resilience than others. MSG, HSG and EHSG did not differ with regard to resilience and well-being. Our results suggest that, university students are able to maintain their functionality by coping with stress in some way, no matter how stressful they are. These findings are discussed in relation to the relevant literature.